Cold-inducible protein RBM3 protects neuroblastoma cells from retinoic acid-induced apoptosis via AMPK, p38 and JNK signaling. (August 2017) - Ma, Shuang-Ping; Ju, Fei; Zhang, Ya-Ping; Shi, Xiang; Zhuang, Rui-Juan; Xue, Han; Ma, Jian; Wang, Lei; Cheng, Bin-Feng; Cao, Hong; Feng, Zhi-Wei; Wang, Mian; et al.
Highlights: Excessive RA leads to neural cell apoptosis, suggesting vitamin A abuse is toxic. Overdose of RA induces neural cell apoptosis by p38 and JNK signaling. RA-induced apoptosis in neural cells can be prevented by mild hypothermia. RBM3 mediates mild hypothermia-conferred neuroprotection. RBM3 attenuates RA's toxicity by affecting AMPK, p38 and JNK pathways. Abstract: As a result of vitamin A abuse, excessive retinoic acid can induce apoptosis in neural cells. Mild-hypothermia and cold-inducible protein RBM3 protect neural cells from apoptosis. However, whether hypothermia/RBM3 protect neural cells from retinoic acid-induced apoptosis remains unclear. The SH-SY5Y neuroblastoma cell line, a common neural cell model of apoptosis, was employed here. Interestingly, retinoic acid overdose induced apoptosis in SH-SY5Y cells, which was prevented by mild-hypothermia. When RBM3 was silenced, hypothermia-related protection was completely abolished. RBM3 overexpression significantly prevented retinoic acid-induced apoptosis. Screening of signaling pathways revealed that RBM3 overexpression markedly inhibited retinoic acid-induced upregulation of p38 and JNK signaling, and antagonized downregulation of AMPK signaling. Subsequent assays demonstrated that p38 and JNK signaling were pro-apoptotic, while AMPK was anti-apoptotic. Overall, these data showed that mild-hypothermia protects neural cells from retinoic acid-induced apoptosis via induction of RBM3, which subsequently mediates the neuroprotective effects via AMPK, p38 and JNK signaling.